Norm Clash in Lex Superior Derogate Legi Inferiori Principle's Implementation on Circular Letters and Laws - Wijayanti, Sri; Sari, Zeti Nofita; Salam, Safrin; Firdaus, Arif Ananda (Reformasi Hukum, 2024)
A circular letter is a legal product classified as a beleidregel issued by specific institution, which is general and serves to support certain policies without contradicting the law. This research discusses two important aspects related to: the implication of the principle of lex superior derogat legi inferiori and the conflict of norms between Circular Letters and the Law. This study aims to analyze how the principle is applied in enacting Circular Letters and its impact on the hierarchy of laws and regulations in Indonesia. The research method used is a normative study with a legislative approach and case analysis. The results show that Circular Letters often ignore the principle of lex superior derogat legi inferiori by overriding regulations that have a higher position, which causes norm clashes. This creates legal uncertainty and harms public trust in the legal system. As a legal product, circular letters should comply with the freies ermessen principle to provide flexibility, but still within the corridors of applicable law. In conclusion, stricter supervision is needed to prepare Circular Letters to ensure compliance with the regulatory hierarchy. The recommendation is to strengthen the testing mechanism and understanding of legal principles in drafting Circular Letters to maintain the integrity of the legal system.